Development of a novel and simple method for clinical therapeutic drug monitoring of aminophylline in humans based on a MWNTs-SiO2/Au composite modified screen-printed electrode. Issue 5 (12th January 2016) - Peng, Anlin; Wang, Yuting; Xiao, Jing; Wang, Shi; Ding, Hong
Abstract : Aminophylline is a drug that needs therapeutic drug monitoring in clinical treatment. Abstract : Aminophylline is a drug that needs therapeutic drug monitoring in clinical treatment. A novel disposable screen-printed electrode (SPE) modified with MWNTs-SiO2 /Au composites for the determination of aminophylline concentration in blood samples was developed. The electrochemical performance of aminophylline at the MWNTs-SiO2 /Au SPE was explored by cyclic voltammetry (CV) and square wave voltammetry (SWV). The optimum experimental conditions were obtained and the currents of aminophylline presented a good linear property with the increasing of the concentrations under optimized conditions. The linear range of aminophylline was from 5 μM to 200 μM with a detection limit of 0.5 μM (S/N = 3). The results of clinical blood samples showed good sensitivity and selectivity of the prepared sensor. Moreover, the drug concentration-time curve of aminophylline in clinical patients was attained at different time points such as 0.5 h, 1 h, and 2 h by the proposed method. The results strongly suggested that the established sensor could be used for practical monitoring in clinical individualized treatment.